History Education and Conflict Transformation Social Psychological Theories, History Teaching and Reconciliation - Psaltis, Charis; Carretero, Mario; Čehajić-Clancy, Sabina (Springer Nature, 2017)
civil society organisations; textbook studies; history textbooks; textbook writing; post-conflict societies; perpetrators; victims